(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Background and objective: The objective of this study was to detect the incidence of chorioamnionitis in PPROM and to evaluate the pattern of foetal outcome in these cases at a tertiary care hospital in Bangladesh. This study is also aimed to analyze the influence of the demographic variables predisposing to chorioamnionitis in PPROM in a locality. Materials and Methods: This single centre cross-sectional study was conducted on 110 pregnant women with preterm rupture of membranes at a tertiary care hospital in Dhaka, Bangladesh. The study group was divided according to the presence or absence of clinical chorioamnionitis defined as the presence of two or more of the following criteria: maternal temperature >38°C on two or more occasions ³1 h apart, maternal tachycardia (³120 beats/min), uterine tenderness, foul smelling amniotic fluid, maternal leukocytosis ³20,000 mm3 with bands and positive C reactive protein. Antibiotics and tocolysis were used according to the hospital protocols. Foetal outcome was measured on the basis of weight of the baby, and presence of infection (fever), Apgar score and neonatal death. Analysis was performed using SPSS-12. Results: In this study the rate of chorioamnionitis in PPROM was 25.4%.The chorioamnionitis was found to be frequent (57.1%) in younger age group between 1525 years while PPROM without chorioamnionitis was common (53.6%) among the age group between 2635 years. Lower socioeconomic class and history of previous PROM and D&C was commonly associated with chorioamnionitis though statistically insignificant (p>0.05). There were also no significant differences in mean birth weight, Apgar scores at 1 and 5 min, rates of respiratory distress syndrome, between patients with and without clinical chorioamnionitis. However, Majority of the babies born to mother with chorioamnionitis showed higher degree of very low birth weight and foetal infection. Neonatal deaths was also higher in the PPROM with chorioamnionitis as compared to the other (32.1% verses 24.3%), though statistically insignificant. In cases of clinical chorioamnionitis the neonates stayed longer in the neonatal intensive care unit (NICU). Conclusion: The risk of chorioamnionitis in PPROM is relatively higher in our locality. Adverse foetal outcome is more frequent in patients with clinical chorioamnionitis in PPROM. Strategies should be developed to reduce the incidence of chorioamnionitis in PPROM and to ensure safer foetal outcomes in such cases. Regular prenatal care may prove as an effective tool in identification of high risk groups in this regard. DOI: http://dx.doi.org/10.3329/bjog.v26i1.13752 Bangladesh J Obstet Gynaecol, 2011; Vol. 26(1) : 10-19